Chronic predation risk affects prey escape abilities through behavioral and physiological changes. (16th December 2021) - Jermacz, Łukasz; Kletkiewicz, Hanna; Poznańska-Kakareko, Małgorzata; Klimiuk, Maciej; Kobak, Jarosław
Abstract: One of the options to reduce predation risk is reallocation of energy into locomotion system. The higher aerobic capacity, the more energy can be partitioned into an escape. Thus, increase in aerobic capacity can increase prey escape abilities. We investigated prey (freshwater crustaceans: Dikerogammarus villosus and Gammarus jazdzewskii ) ability to improve their locomotor performance through an increase in aerobic capacity under chronic predation risk. We forced gammarids (pre-exposed to the predation cue or control) to long-distance swimming in the presence or absence of predation cues to obtain: control (pre-exposure and test in control conditions), acute (pre-exposure to control conditions, test in the presence of the predation cue) and chronic (pre-exposure and test in the presence of the cue) risk treatments. After this forced swimming effort, we measured various swimming parameters, glycogen content, and lactate concentration of the experimental amphipods. Exposure to predation cues made G. jazdzewskii reduce its speed after prolonged forced swimming in the presence of predation cues, whereas D. villosus never changed its swimming performance due to predation risk. In both species, post-effort lactate concentration was higher under the acute predation risk than in risk-free conditions. However, only D. villosus demonstrated lower lactate concentration when exposed to chronic vs. acute predation risk. Moreover, pre-exposure of both species to predation cues caused reduction in glycogen content. We showed that under chronic predation risk some prey species can modify their physiology to increase aerobic capacity and sustain high efficiency of escape performance. However, this phenomenon is species-specific and costly. Abstract : We showed that prey individuals chronically exposed to predation risk can improve their physical capacity, being able to respond to predator presence more efficiently. However, this ability seems to be species-specific, and the locomotor performance of some prey species may worsen after a long-term exposure to predators. Thus, chronic predation risk may affect the community functioning by changing outcomes of interspecific interactions.